Successful Conservative Management of a Dislocated IUD - Hasan Ali Inal; Zeynep Ozturk Inal; Ender Alkan (Hindawi Limited, 2015)
Background. Intrauterine contraceptive devices (IUDs) are widely utilized all over the world owing to their low cost and high efficacy. Uterine perforation is a rare complication that may occur at IUD insertion resulting in extrauterine location of the IUD. Traditionally, surgical removal of dislocated IUDs has been recommended. Case. A 68-year-old patient who had an IUD (Lippes loop) inserted 32 years ago and whose routine examination incidentally revealed a dislocated IUD in the abdominal cavity. The patient remained asymptomatic during three years of follow-up and the IUD was left in place. Conclusion. Asymptomatic patients, whose vaginal examinations and ultrasonography or X-ray results reveal a dislocated IUD, may benefit from conservative management.